The Treasury Stock Method and Conventional Method in Reciprocal Stockholdings - An Amalgamation: A Comment. - Chen, Raymond S. (The Accounting Review, 1975)
This article focuses on an article which was published in the April 1974 issue of the journal "The Accounting Review," which discussed three methods of allocation in reporting controlling and minority earnings on the consolidated income statement by simultaneous equations. The article demonstrated that the traditional treasury stock method in reciprocal stockholding situations understates the minority interest and is not consistent with a true treasury stock approach, and suggested the inclusion of additional earnings per share figures in revealing the current per-share equity claim of two equity interests on current earnings. The purpose of this article is to demonstrate that the two alternative models of allocating total consolidated net income to controlling and minority interests, proposed in the article published earlier, were improperly constructed and were not valid, and to illustrate the inefficiency in communicating the effective earnings per share of minority interests of subsidiaries through consolidated financial statements of the parent company.